Psychological, social, and physical ecologies for child resilience: a South African perspective - Pillay, Jace (Frontiers in Psychology, 2023)
Children live in a complex world surrounded by global concerns such as climate change, economic instability, threats of terrorism and war. However, in South Africa, one may note that children face several additional challenges including high unemployment rates in families, exposure to violence, living in conditions of poverty, exposure to HIV/AIDS, and high levels of orphanhood. Compounding these problems is the economic situation in the country where the government is unable to provide adequate support for children in various domains. Understanding the mechanisms through which children successfully adapt to their environments and transition into adulthood are important to understand. Resilience research seeks to understand these mechanisms and underlying processes that enable some individuals to recover from adversity against all odds. Therefore, there is an increased movement not only toward understanding resilience processes in children, which enable them to develop into fully functional and upstanding citizens of society despite the adversities they face, but also how resilience research can be translated into practice to be used by service professionals such as psychologists, school counselors, social workers, and teachers. Adopting a socioecological understanding of resilience, the author reviews literature on the psychological, social, and physical ecologies for child resilience globally. Special emphasis is placed on the ecologies of child resilience within the African context and South Africa in particular. A socioecological perspective positions child resilience within four important levels, namely individual, relationships, community, and society. The salient features of child resilience within a South African context are discussed within the four levels highlighting the implications for interventions to promote child resilience. The implications have global value because child resilience is a phenomenon that needs global attention.